Tacrolimus-Induced Neurotrophic Differentiation of Adipose-Derived Stem Cells as Novel Therapeutic Method for Peripheral Nerve Injury - Yao, Xiangyun; Yan, Zhiwen; Li, Xiaojing; Li, Yanhao; Ouyang, Yuanming; Fan, Cunyi (Frontiers in Cellular Neuroscience, 2021)
Peripheral nerve injuries (PNIs) are frequent traumatic injuries across the globe. Severe PNIs result in irreversible loss of axons and myelin sheaths and disability of motor and sensory function. Schwann cells can secret neurotrophic factors and myelinate the injured axons to repair PNIs. However, Schwann cells are hard to harvest and expand in vitro, which limit their clinical use. Adipose-derived stem cells (ADSCs) are easily accessible and have the potential to acquire neurotrophic phenotype under the induction of an established protocol. It has been noticed that Tacrolimus/FK506 promotes peripheral nerve regeneration, despite the mechanism of its pro-neurogenic capacity remains undeﬁned. Herein, we investigated the neurotrophic capacity of ADSCs under the stimulation of tacrolimus. ADSCs were cultured in the induction medium for 18 days to differentiate along the glial lineage and were subjected to FK506 stimulation for the last 3 days. We discovered that FK506 greatly enhanced the neurotrophic phenotype of ADSCs which potentiated the nerve regeneration in a crush injury model. This work explored the novel application of FK506 synergized with ADSCs and thus shed promising light on the treatment of severe PNIs.